E-Learning y su incidencia en el autoaprendizaje de los alumnos de décimo año de la Unidad Educativa Réplica Eugenio Espejo del cantón Babahoyo, Provincia Los Ríos - Pita Medranda, Byron Styvens (2019)
The research work is presented by the need of teachers and students of the Replica Educational Unit "Eugenio Espejo", in implementing new technological tools that contribute to the acquisition of new content in an interactive and participatory way that helps to better self-learning, that is to say the construction of new knowledge, in the institution there are adequate means to conduct talk and training on information and communication technologies, but through observation and conversing with teachers, these do not occur frequently. Management is no longer just the task of the teacher, but also of the educational platforms that must be integrated to improve the learning experience, fulfilling the objectives of the class and students can share their concerns, for this reason teachers must transform their way of Teaching educational institutions Educational institutions must develop a true vision of their establishment based on innovation and continuous learning. From the results obtained by the survey of students and teachers, it was concluded that with the help of an educational guide on information and communication technologies E-learning and especially on the GoConqr platform, teachers will be trained on innovative technological resources provided by the web, which allows teachers to integrate new strategies for the teaching-learning process of students, motivating them to seek constant information about the information and communication technologies that they can contribute in their training process, to obtain a positive result in your academic performance